Aplikasi Akuntansi Simpanan Anggota Pada KUD Bangkit Abadi Desa Bandorasawetan - Yoanna Yoanna; Widya Jati Lestari; Marsani Asfi; Noerrochmani Aswita Dian Irijanti Mintarsih (Fakultas Ekonomi dan Bisnis, Universitas Catur Insan Cendekia, 2021)
The Bangkit Abadi Village Unit Cooperative (KUD) is a cooperative located in Bandorasawetan Village, whose main activity is providing savings services for cooperative members with the aim of prospering cooperative members and the surrounding community. With the existence of this cooperative, it is hoped that it will create a desire and increase public awareness to save. This KUD does not yet have a good computerized system. Therefore, there are still some obstacles in KUD Bangkit Abadi in terms of new member registration activities and member savings. These activities will run smoothly if supported by a good system and by implementing a good internal control system in cooperatives, so as to prevent errors in data processing. The procedures that apply to the KUD include related parts, namely registration, member data, internal control systems, and documents used. The analysis and design stages of the application system are described using flowcharts, Data Flow Diagrams (DFD), Entity Relationship Diagrams (ER-Diagrams) and developed using MySQL database as a programming language. This relationship is narrated into several diagrams, namely: context diagrams, data flow diagrams level 0 and level 1, relationships between entities, and relationships between tables used. The results obtained from the design of this application are in the form of member book reports, savings data reports, and general journal reports as a form of description of the activities of new member registration and member savings at the Bangkit Abadi Village Cooperative Unit.Key words: Applications, Accounting, Savings, Cooperatives